Doctrinal Effect: Implikasi Yuridiksi Ekstrateritorial Hukum Persaingan Usaha - Esternella, Milka Belatrix (Legal Spirit, 2023)
The Effects Doctrine creates an important basis for the application of local law outside of its territory. It reflects the understanding that in this day and age, actions taken in one jurisdiction can significantly affect other jurisdictions. The use of competition law extraterritorial jurisdiction, based on the effects doctrine, has long been debated. The purpose of this study is to discuss the application of extraterritorial jurisdiction to competition law in Indonesia. This research uses the normative juridical method to analyze legal norms and principles. The approaches used include statutory approach, comparative law approach, and case approach. The result of this research is that regulations regarding the prohibition of monopolistic practices and unfair business competition have not explicitly regulated extraterritorial norms in Indonesia. However, the Business Competition Supervisory Commission made a legal breakthrough by applying the extraterritorial principle to resolve the involvement of foreign business actors and impose sanctions on them. This article argues that Indonesia significantly needs to amend its competition law and increase cooperation with other countries to enforce competition law.